STUDY OF THE EFFECTIVENESS OF VARIOUS METHODS OF PLASTIC POST-TRAUMATIC CRANIAL DEFECTS. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The purpose of this work is to study the significance of clinical and neurological symptoms and evaluate the effectiveness of using various methods of plastic surgery of post-traumatic defects of the cranial vault